MAINSTREAMING HUMAN RIGHTS THROUGH THE ENLARGEMENT POLICY: THE CASE OF THE WESTERN BALKAN COUNTRIES - Skara, Gentjan (Novos Estudos Jurídicos, 2021)
The EU enlargement has been considered as the EU’s most efficient foreign policy instrument in terms of its ability to transform communist countries into functional democracies and open market countries. Since the beginning of 1990s, the promotion of human rights has become prominent topic either for the consolidation of human rights within the EU or outside. The argument of this paper is that the EU enlargement policy has influenced Western Balkan countries to improve their domestic legislation in the area of human rights. The paper demonstrates, firstly, how has evolved the EU human rights actorness from the establishment of the EE Community and secondly, discuss strategies and instruments used by the EU to export its norms and values in the Western Balkan countries. The paper addresses the following research question: how, whether and to what extent, the EU has promoted human rights in the Western Balkan countries. Throughout this paper, a doctrinal legal research has been used to analyze EU primary and secondary sources. The value of this paper lies in its comprehensiveness in drawing a complete picture of EU role in promoting human rights in Western Balkan countries through enlargement policy and to discuss the impact of the EU Charter of Fundamental Rights in the candidate countries.